POLA PEMBERDAYAAN KELOMPOK WANITA TANI MELALUI PENINGKATAN NILAI EKONOMI INDUSTRI GADUNG (Studi Kasus Di Kecamatan Kalidawir Kabupaten Tulungagung) - MUFIDA DIAH LESTARI (Jurnal AGRIBIS, 2020)
Abstract Efforts to improve the economy of farm-household families through efforts to empower women farmers' groups through improving the economic assessment of the yam industry. The method used in this research is descriptive qualitative. Respondents used in this research were informants from farmer women in Kalidawir District, Tulungagung Regency. The pattern of empowerment undertaken is to provide capacity building to these women's groups so that they can provide economic assistance to their families. Capacity strengthening is carried out by providing training on how to process the yam into a variety of flavors, providing socialization on more modern packaging, socialization about business licensing and physical forms of assistance such as (machinery, water pumps, frying pans and stoves). With the empowerment of the local government so that it can encourage the groups of women farmers to be more creative. Keywords: empowerment patterns, farm women, yam